A RESISTANCE TO LEPTIN IN DEVELOPMENT OF DIFFERENT OBESITY PHENOTYPES - A. V. Ott; G. A. Chumakova; N. G. Veselovskaya (Российский кардиологический журнал, 2016)
The underlying process of visceral obesity (VO) is frequently the resistance to regulating action of leptin on the patients food related behavior. There is ongoing research on the role of soluble leptin receptors (SLR) in the leptin signal transmittance and leptin resistance development (LR).Aim. To study the relation of leptin metabolism parameters with insulin resistance (IR) in men with various obesity phenotypes.Material and methods. Totally, 110 males included of the age 44-67 y.o., with arterial hypertension, absence of atherosclerosis of any area signs, and diabetes. The participants were selected to two groups according to metabolic obesity phenotype by the value of epicardial fat thickness (EFT) and body mass index. In groups we assessed the levels of insulin, HOMA-IR, serum leptine (SL), SLR and free leptin index (FLI) calculated as SL/SLR, lipid profile including apoproteines A1 and B (ApoA1, ApoB). EFT was measured via echocardiography.Results. It has been shown, that leptin metabolism disorders and LR might lead to metabolically stout phenotype (MSP) and its main complication — IR. The regression equation is formulated that links FLI with HOMA-IR.Conclusion. Leptin metabolism disorder is related to the development of VO and IR. FLI can be used as laboratory marker of LR, as an early marker of IR risk and, possibly, further cardiometabolic complications.